The Effectiveness of Higher Education Financing Management in an Effort to Improve the Quality of Students at Teuku Umar University in West Aceh - Andhiyani Muhadi; Masduki Ahmad (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
To improve the quality of education, consistent encouragement for progress and improvement is essential. The notion of quality is paramount in the field of education and is addressed through continuous improvement. It serves as a solution to address the problem of low-quality education that relies on traditional methodologies. Total Quality Management is a comprehensive approach to quality management that involves every level of management and every department in an organization. In an organizational system that seeks to provide satisfactory customer service, it is important to implement a set of guidelines that ensure consistent customer satisfaction is met. These guidelines should be designed to facilitate the prompt resolution of customer complaints and concerns, while promoting a positive and friendly atmosphere for all customers. There are four key components to effective management in higher education, the first being ensuring that students are satisfied with the level of service provided. The concept of higher education can be divided into three core aspects. First, it involves the pursuit of education outside of secondary school.